Predictors of voice outcome in pediatric non‐selective laryngeal reinnervation. (9th September 2019) - Ongkasuwan, Julina; Espinosa, Maria Catalina L.; Hollas, Sarah; Devore, Danielle; Procter, Teresa; Bassett, Ethan; Schwabe, Aloysia
Abstract : Objectives: Non‐selective laryngeal reinnervation (NSLR) using the ansa cervicalis to the recurrent laryngeal nerve (RLN) is a promising treatment option for pediatric unilateral neuronal vocal fold movement impairment (VFMI). The aim is to describe our clinical outcomes with this technique and to identify preoperative characteristics that may predict postoperative voice outcomes. Methods: This is a cohort study of pediatric patients with unilateral neuronal VFMI, who underwent NSLR from March 2012 to July 2018. Pre‐ and postoperative Pediatric Voice Related Quality of Life (PVRQOL) questionnaires, Consensus Auditory Perceptual Evaluation of Voice (CAPE‐V) ratings, and objective voice measures were obtained. In addition, patients underwent preoperative laryngeal electromyography (LEMG). Results: Thirty‐two patients were identified. Twenty‐one had complete data sets for analysis. The mean duration of VFMI was 9.02 years (range 1.1–26.1 years). There were significant improvements in PVRQOL ( P = .0005), in all CAPE‐V subsets ( P  ≤ .0001 to .0195), mean and maximum intensities ( P = .0342 and 0.0110, respectively), cepstral peak prominence ( P = .0001), and cepstral spectral index of dysphonia ( P  ≤ .0001). A worse preoperative LEMG correlated with a greater change in maximum phonation time ( P = .0162) and maximum intensity ( P = .0346). Age at injury and duration of injury had no significant impact on voice outcomes; however, patients with concurrent posterior glottic insufficiency did have smaller changes in PVRQOL ( P = .012). Conclusion: NSLR is an effective treatment for pediatric unilateral neuronal VFMI even many years after initial RLN injury. LEMG may help predict voice outcomes of reinnervation in pediatric patients, but further data is still needed. Level of Evidence: 4 Laryngoscope, 130:1525–1531, 2020